One-pot fabrication of ferric ferrocyanide functionalized graphene hydrogel for cesium removal in aqueous solution. Issue 71 (21st September 2017) - He, Yan-Rong; Yang, Yang; Huang, Zhao-Ya; Wang, Wei-Juan; Li, Xiao-Long; Zhang, Peng-Hao; Tan, Zhao-Yi; Zhang, Dong
Abstract : A novel ferric ferrocyanide functionalized graphene hydrogel was fabricated and was used for cesium removal in aqueous solution. Abstract : The rapid development of the nuclear industry brings benefits for global economic development and solves the energy crisis. However, nuclear industrial activities produce a large amount of radioactive wastewater, which poses serious threats to environmental safety and human health, and 137 Cs is considered one of the most abundant radionuclides in radioactive wastewater. In this study, we fabricated a new type of ferric ferrocyanide (Prussian blue, PB) functionalized graphene hydrogel (PB/rGOH) for Cs(i ) removal. The as-prepared PB/rGOH shows a three dimensional network with PB nanoparticles uniformly distributed on the surface of the rGO sheets. The PB/rGOH could be readily separated from aqueous solution. Moreover, the volume of the composite could shrink to a small stiff bulk material, further reducing the volume of the waste. Kinetics experiments showed that Cs(i ) adsorption on PB/rGOH fitted well with pseudo-second-order kinetic model, and the equilibrium data agreed well with the Langmuir model. As calculated from the Langmuir model, the maximum adsorption capacity at pH 5.0 is 58.82 mg g −1 . The increase of pH from 3 to 7 could enhance the adsorption capacity, however, further increasing the pH value resulted in serious decomposition of PB nanoparticles. In conclusion, the PB/rGOH prepared in our work showed good performance on removal of Cs(i ) in aqueous solution, and has a good application prospect in radioactive waste water treatment.